Description of Knowledge and Behavior Levels About Breast Examination (Best Self-Examination) in Adolescent Women - Haina Maulani; Hanna Maulida; Ismiatun Jariyah; Nabilla Putri Jullizir (Fakultas Kesehatan Masyarakat Universitas Muhammadiyah Jakarta, 2021)
Breast self-examination (BSE) is done by feeling and looking at the breast itself to see the possibility of physical changes in the breast. This process is carried out so that all changes that lead to more serious conditions can be detected early. Breasts will generally feel different during menstruation. Before and during this period, most women feel that their breasts are getting tighter and denser. Therefore, women need to do a breast self-examination (BSE) every 1 month, to find out whether there is a change in the shape of the breast from time to time. This study aims to determine the level of knowledge and behavior about breast self-examination (Aware) in young women. The research used is qualitative research using a descriptive observational study design, namely conducting in-depth interviews with 4 informants which are by the interview guidelines. Based on the results of the study, 4 respondents had been interviewed according to the addresses of their respective researchers, respondents according to the characteristics of the study. And respondents have good enough knowledge about breast self-examination (BSE), respondents also behave to check their breasts regularly after menstruation.